Some Aspects of Automated Implementation of Dependencies in PHP Language - Tkachenko, Olha; Rusakov, Mykyta (Cifrova platforma: ìnformacìjnì tehnologìï v socìokulʹturnìj sferì, 2021)
The purpose of the article is to research, analyze and consider the general problems and prospects of using the principle of implementing dependencies in the development of web applications in the PHP language. Research methods are methods of semantic analysis of the basic concepts of this subject area (web technologies and web applications). The article considers the existing approaches to control inversion based on the use of the dependency implementation template. The novelty of the research is to solve the control inversion problems based on a template when designing web applications. The conclusion of the research conducted in the article is that the existing problems and prospects for the application of the principle of dependency implementation in web applications with program code written in PHP have been analyzed. Taking into account the results of the analysis, the authors have developed a system for automating the implementation of dependencies, which is important for solving problems of improving the efficiency of web application development processes in PHP.